Neural bases for the genesis and CO2 therapy of periodic Cheyne–Stokes breathing in neonatal male connexin-36 knockout mice - Casarrubios, Ana M.; Pérez-Atencio, Leonel F.; Martín, Cristina; Ibarz, José M.; Mañas, Eva; Paul, David L.; Barrio, Luis C. (Frontiers in Neuroscience, 2023)
Periodic Cheyne-Stokes breathing (CSB) oscillating between apnea and crescendo-decrescendo hyperpnea is the most common central apnea. Currently, there is no proven therapy for CSB, probably because the fundamental pathophysiological question of how the respiratory center generates this form of breathing instability is still unresolved. Therefore, we aimed to determine the respiratory motor pattern of CSB resulting from the interaction of inspiratory and expiratory oscillators and identify the neural mechanism responsible for breathing regularization induced by the supplemental CO2 administration. Analysis of the inspiratory and expiratory motor pattern in a transgenic mouse model lacking connexin36 electrical synapses with a persistent CSB revealed that the reconfiguration between apnea and hyperpnea results from cyclical turn on/off of active expiration driving by the expiratory oscillator, which acts as a master pacemaker of respiration and entrains the inspiratory oscillator to restore ventilation. The results also showed that the suppression of CSB by supplemental CO2 is due to the stabilization of coupling between expiratory and inspiratory oscillators, which causes the regularization of respiration. Periodic breathing rebooted after washout of CO2 excess when the inspiratory activity depressed again profoundly, indicating that the disability of the inspiratory oscillator to sustain ventilation is the triggering factor of CSB. Under these circumstances, the expiratory oscillator activated by the increase of CO2 behaves as an “anti-apnea” center generating the crescendo-decrescendo hyperpnea and periodic breathing. The neurogenic mechanism of CSB identified highlights the plasticity of the two-oscillator system in the neural control of respiration and provides a rationale base for CO2 therapy.